Computationally efficient modelling of tidal rivers using conceptual reservoir-type models. (March 2016) - Meert, Pieter; Pereira, Fernando; Willems, Patrick
Abstract: Conceptual reservoir-type models of river systems, that mimic the results of detailed hydrodynamic models, provide a powerful tool for numerous river management applications. Thanks to their computationally efficient model structure they are very well suited for applications that require long term simulations or a large number of model iterations. However, one well-known problem is that conceptual models have difficulties to account for backwater effects. For this reason, their application to tidally influenced river reaches so far was almost non-existent. This paper introduces an extension of an existing grey-box reservoir modelling technique to incorporate tidally influenced river reaches. The methodology is demonstrated for the downstream part of the rivers Zenne and Rupel in Belgium. Results show a minor loss of accuracy when the detailed model is replaced by the surrogate conceptual model. Also, the tidal effects are well represented. Highlights: A surrogate modelling approach for tidally influenced river reaches is developed. The approach is modular, flexible and compatible with other reservoir-type models. A discrete and explicit calculation scheme that allows for very short calculation times is used. A case study of the rivers Zenne and Rupel in Belgium was used to demonstrate the accuracy of the modelling approach.